An Inquiry into Knowledge Management Capabilities and Their Influence on Managerial Decision-Making - Juan Agustino Parulian Sitohang; Miska Irani Br Tarigan; Theresa Sisilia Situmorang (International Forum of Researchers and Lecturers, 2025)
This study investigates the role of knowledge management (KM) capabilities in enhancing managerial decision-making within organizational settings. Using a systematic review approach, ten peer-reviewed journals published between 2019 and 2024 were analyzed to identify key themes, patterns, and empirical findings related to knowledge management implementation and its influence on decision-making processes. The review reveals that strong knowledge management capabilities particularly in knowledge acquisition, storage, sharing, and utilization significantly contribute to improving the accuracy, speed, and strategic quality of managerial decisions. The findings also show that organizations with well-developed knowledge management infrastructures, supported by digital technologies and a culture of knowledge sharing, demonstrate greater adaptability, innovation, and problem-solving effectiveness. This study concludes that knowledge management capabilities are essential for strengthening evidence-based decision-making and enhancing organizational competitiveness. Implications for managers emphasize the need to invest in knowledge management systems and foster collaborative knowledge practices. Suggestions for future research include expanding the scope to cross-industry comparisons and integrating knowledge management with emerging technologies such as AI-based decision support systems..